Please help me simplify these expressions. 1. (x/y)^-3 2. (4t)^-2 t^0/t^6 v^-8 3. p^-3/p^-2 r^3 4. (5x-7)^2

### 1 Answer | Add Yours

1. ` (x/y)^-3`

According to the negative exponent rule `a^-n=1/a^n` , this says that negative exponents in the numerator get moved to the denominator and become positive exponents.

`=1/(x/y)^3`

`=1/x^3/y^3`

`=y^3/x^3`

` `

**This is the required answer.**

**Sources:**

### Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes